2019
DOI: 10.2147/ijn.s198583
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antibacterial and osteogenesis performances of LL37-loaded titania nanopores in vitro and in vivo</p>

Abstract: Background: Many studies have shown that the size of nanotube (NT) can significantly affect the behavior of osteoblasts on titanium-based materials. But the weak bonding strength between NT and substrate greatly limits their application. Purpose: The objective of this study was to compare the stability of NT and nanopore (NP) coatings, and further prepare antibacterial titanium-based materials by loading LL37 peptide in NP structures. Methods: The adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 47 publications
(43 reference statements)
1
28
0
Order By: Relevance
“…Bacterial infection is one of the most serious problems for clinical application of the implantable biomaterials, which is the primary cause of implantation failure. 29 Implantable biomaterials with antibacterial performances can inhibit bacterial infection, and thus maintain long-term stability of the implants. 30 Previous studies have shown that -SO 3 H groups on biomaterials could reduce bacterial adhesion and prevent bacteria from biofilm formation, showing antibacterial performances.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection is one of the most serious problems for clinical application of the implantable biomaterials, which is the primary cause of implantation failure. 29 Implantable biomaterials with antibacterial performances can inhibit bacterial infection, and thus maintain long-term stability of the implants. 30 Previous studies have shown that -SO 3 H groups on biomaterials could reduce bacterial adhesion and prevent bacteria from biofilm formation, showing antibacterial performances.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SEM and confocal fluorescence images showed neuron‐like cell shape, with several neuritic extensions, whereas for substrates with larger pores, the cell cytosol appears with no preferred direction. Many studies reported the fabrication of nanopores on the titanium (Ti) surface applied in bone implants (Ketabchi, Komm, Miles‐Rossouw, Cassani, & Variola, ; Louarn, Salou, Hoornaert, & Layrolle, ; Pan et al, ; SchĂźrmann et al, ; Shen et al, ; Sun, Liu, Wu, & Huang, ; Zhuang, Zhou, & Yuan, ). For instance, oxidative nanopatterning (Bellod et al, ; Lauria et al, ) and electron beam lithography (EBL; Garoli et al, ) can be applied to form nanopores on Ti alloys.…”
Section: Nanoporesmentioning
confidence: 99%
“…Furthermore, it was proven that the p38 MAPK pathway also modulates the proliferation and osteogenic differentiation of human bone-derived marrow mesenchymal stem cells. 28 There are few reports about hBD3 and osteogenesis; however, other cationic antimicrobial peptides, such as LL37, have been found to affect the proliferation and differentiation of MC3T3-E1 cells 29 and to enhance bone regeneration in a rat calvarial bone defect through the p38 MAPK pathway. 30 Therefore, we hypothesized that the p38 MAPK pathway might also modulate the osteogenic process of hBD3 gene-modified hPDLCs.…”
Section: Introductionmentioning
confidence: 99%